BILATERAL GYNANDROMORPHY IN AGAPORNIS SP. (PSITTACIFORMES: PSITTACULIDAE) - Muñoz-Gil, Jorge (2015)
Bilateral gynandromorphy (BGA) is a rare state in which an individual exhibits both male and female traits. Gynandromorphy is exceptional in birds, but has been observed in a number of avian families, and is most commonly reported in the Passeriformes. The general pattern in BGA is female plumage characters on the left side and male characters on the right, corresponding to the orientation of the ovary and testis in birds. We documented observations of a bilateral gynandromorph in a captive love bird (Agapornis spp.), product of two forms: “lutino” (fischeri group), with yellow body, orange head, bright red bill, and bare white circunocular area x“cremino” (roseicollis group), with white body, bill cream colored, no eyering. The bird exhibited the typical yellow and bright orange color of a lutino form on the right half of its body, and the white appearance of a cremino form on the right half, with red bill, and bare white circunocular area.